2019
DOI: 10.1158/1538-7445.am2019-586
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 586: CD4+and CD8+T cells influence 4T1.2luc mammary tumor growth and survival

Abstract: The 4T1.2 syngeneic murine breast cancer model is an aggressive model of stage IV triple-negative breast cancer. Despite its significant strength, the 4T1.2 model is poorly immunogenic with few defined tumor antigens. The firefly luciferase gene, luc2, has been transfected into various tumor cell lines as a reporter for bioluminescence imaging. However, studies have shown that the luciferase (Luc) may serve as a tumor antigen and induce CD8+ cytotoxic T cell responses. The goal of the current study was to dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Studies using the 4T1 breast cancer model have demonstrated that luciferase likely acts as an antigen, leading to the restriction of tumor cell growth and metastasis as a result of T cell activities. 87 , 88 In contrast to these findings, a study using the ID8 model of ovarian cancer showed no effect of luciferase expression on tumor engraftment or the tumor immune microenvironment. 89 Similarly, in the GBM GL261 model, Clark et al showed no difference in proliferation, cytokine expression, invasive characteristics, CD3+ cell infiltration, or in vivo growth between tumor cells expressing luciferase and those without luciferase.…”
Section: Syngeneic Murine Models Of Gbmmentioning
confidence: 86%
“…Studies using the 4T1 breast cancer model have demonstrated that luciferase likely acts as an antigen, leading to the restriction of tumor cell growth and metastasis as a result of T cell activities. 87 , 88 In contrast to these findings, a study using the ID8 model of ovarian cancer showed no effect of luciferase expression on tumor engraftment or the tumor immune microenvironment. 89 Similarly, in the GBM GL261 model, Clark et al showed no difference in proliferation, cytokine expression, invasive characteristics, CD3+ cell infiltration, or in vivo growth between tumor cells expressing luciferase and those without luciferase.…”
Section: Syngeneic Murine Models Of Gbmmentioning
confidence: 86%